2017
DOI: 10.1128/mbio.01514-17
|View full text |Cite
|
Sign up to set email alerts
|

Role of Granulocyte-Macrophage Colony-Stimulating Factor Production by T Cells duringMycobacterium tuberculosisInfection

Abstract: Mice deficient for granulocyte-macrophage colony-stimulating factor (GM-CSF−/−) are highly susceptible to infection with Mycobacterium tuberculosis, and clinical data have shown that anti-GM-CSF neutralizing antibodies can lead to increased susceptibility to tuberculosis in otherwise healthy people. GM-CSF activates human and murine macrophages to inhibit intracellular M. tuberculosis growth. We have previously shown that GM-CSF produced by iNKT cells inhibits growth of M. tuberculosis. However, the more gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(79 citation statements)
references
References 77 publications
2
76
1
Order By: Relevance
“…Given the differences between IFNγ‐sufficient and ‐deficient immunopathology, this model allowed the identification of some important IFNγ‐driven immunoregulatory networks. The elevated GM‐CSF was of particular interest to us given the extensive neutrophilia, the role of CD8+ T cells in driving disease, and the fact that GM‐CSF is made by CD8+ T cells . Indeed, we showed that IFNγ −/− Prf1 −/− mouse CD8+ T cells expressed elevated levels of GM‐CSF, and that exogenous administration of IFNγ regulated this production.…”
Section: Discussionmentioning
confidence: 86%
“…Given the differences between IFNγ‐sufficient and ‐deficient immunopathology, this model allowed the identification of some important IFNγ‐driven immunoregulatory networks. The elevated GM‐CSF was of particular interest to us given the extensive neutrophilia, the role of CD8+ T cells in driving disease, and the fact that GM‐CSF is made by CD8+ T cells . Indeed, we showed that IFNγ −/− Prf1 −/− mouse CD8+ T cells expressed elevated levels of GM‐CSF, and that exogenous administration of IFNγ regulated this production.…”
Section: Discussionmentioning
confidence: 86%
“…NK T cells (NKT cells) are a heterogeneous group of T cells that share properties of both T cells and NK cells. Upon stimulation, NKT cells can secrete plenty of IL‐4, IL‐13, IFN‐γ, GM‐CSF, and other cytokines and chemokines to display the antitumor and immune modulation activities . As reported, the secretion of TGF‐β by MDSCs inhibits the activation of NK cells by decreasing the expression of NKG2D .…”
Section: Main Functional Characteristics Of Mdscsmentioning
confidence: 83%
“…These cells appear to be capable of directly killing extracellular Mtb via release of granulysin and intracellular Mtb via granulysin and perforin. 16 Clearly, the Vc9Vd2 T-cell subset is important in the human immune response to Mtb, but further work is required to evaluate the role of various cytokines in protection from disease at different timepoints during infection. 13 In the mouse model, although cd T cells seem to be less essential to immunity against Mtb, 14,15 GM-CSF production by cd T cells in the lungs seems to play a role in protection and an additive effect between GM-CSF and IFNc promoted macrophage control of intracellular bacterial replication.…”
Section: Mycobacteria and Other Bacterial Infectionsmentioning
confidence: 99%
“…13 In the mouse model, although cd T cells seem to be less essential to immunity against Mtb, 14,15 GM-CSF production by cd T cells in the lungs seems to play a role in protection and an additive effect between GM-CSF and IFNc promoted macrophage control of intracellular bacterial replication. 16 Clearly, the Vc9Vd2 T-cell subset is important in the human immune response to Mtb, but further work is required to evaluate the role of various cytokines in protection from disease at different timepoints during infection.…”
Section: Mycobacteria and Other Bacterial Infectionsmentioning
confidence: 99%